2003
DOI: 10.1101/lm.63903
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Contacts Among Sensory, Motor, and Serotonergic Neurons in the Pedal Ganglion of Aplysia

Abstract: Present models of long-term sensitization in Aplysia californica indicate that the enhanced behavioral response is due, at least in part, to outgrowth of sensory neurons mediating defensive withdrawal reflexes. Presumably, this outgrowth strengthens pre-existing connections by formation of new synapses with follower neurons. However, the relationship between the number of sensorimotor contacts and the physiological strength of the connection has never been examined in intact ganglia. As a first step in address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 46 publications
1
20
0
1
Order By: Relevance
“…Stimuli that produce dishabituation of the withdrawal reflex, such as tail shock, activate facilitatory interneurons, some of which are serotonergic (Glanzman et al, 1989;Mackey et al, 1989;Marinesco and Carew, 2002). Release of 5-HT onto sensory and motor neurons within the CNS of Aplysia (Kistler et al, 1985;Marinesco and Carew, 2002;Zhang et al, 2003) causes rapid-onset presynaptic facilitation via processes that involve PKA and PKC [see Byrne and Kandel (1996) for details]. The strength of the presynaptic facilitatory processes wanes rapidly after washout of 5-HT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimuli that produce dishabituation of the withdrawal reflex, such as tail shock, activate facilitatory interneurons, some of which are serotonergic (Glanzman et al, 1989;Mackey et al, 1989;Marinesco and Carew, 2002). Release of 5-HT onto sensory and motor neurons within the CNS of Aplysia (Kistler et al, 1985;Marinesco and Carew, 2002;Zhang et al, 2003) causes rapid-onset presynaptic facilitation via processes that involve PKA and PKC [see Byrne and Kandel (1996) for details]. The strength of the presynaptic facilitatory processes wanes rapidly after washout of 5-HT.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, serotonergic processes have been shown to contact both sensory and motor neurons within the central ganglia of Aplysia (Kistler et al, 1985;Marinesco and Carew, 2002;Zhang et al, 2003). Finally, release of 5-HT is required for dishabituation and sensitization of the defensive withdrawal reflex in Aplysia (Glanzman et al, 1989).…”
Section: -Ht-induced Facilitation Depends On Postsynaptic Exocytosismentioning
confidence: 99%
“…Therefore, there is a strong correlation between primary SN activation and amplification of 5-HT release. In addition, using confocal microscopy, Zhang et al (2003) showed contacts between tail SNs and serotonergic fibers. Primary SNs therefore appear to be in an ideal position to modulate or trigger 5-HT release locally through axo-axonic contacts.…”
Section: Local Patterns Of 5-ht Releasementioning
confidence: 99%
“…Interestingly, Zhang et al (2003) also determined that serotonergic processes usually make contact with SNs or MNs at sites located at a distance from SN-MN synapses. They proposed that serotonergic transmission in this area is essentially volumic or paracrine (i.e., 5-HT travels over distances of a few hundred micrometers before reaching its postsynaptic targets) [for review on paracrine transmission, see Bunin and Wightman (1999)].…”
Section: Local Patterns Of 5-ht Releasementioning
confidence: 99%
See 1 more Smart Citation